Microstrip-line type bruce array antenna with wide fan beam and high gain. Issue 6 (13th April 2021) - Cho, Hyunyoung; Lim, Seongju; Jo, Hye-Won; Chae, Soo-Chang; Yu, Jong-Won
ABSTRACT: In this letter, a microstrip-line type Bruce array antenna with a wide fan beam and high gain is proposed. The unit composed of the radiating edge and non-radiating edge is repeatedly arranged symmetry to the feeding part. The repeated radiating edge operates as an array of magnetic current sources, which radiates the wide beam pattern in the E-plane and achieves high gain in the H-plane. The far-field radiation pattern and the input impedance according to the number of units was shown. The proposed array antenna has a wide half-power beamwidth (HPBW), simulated result 150.4 ∘ in the E-plane, and has a high peak gain, simulated 10.5 dB. The proposed array antenna with five units was fabricated and measured. The measured HPBW and peak gain were 104.2 ∘ and 10.97 dB, respectively.